Is climate change framed as 'business as usual' or as a challenging issue? The practitioners' dilemma. (August 2016) - Aldunce, Paulina; Handmer, John; Beilin, Ruth; Howden, Mark
There is growing recognition that routine climate change framing is insufficient for addressing the challenges presented by this change, and that different framings of climate change shape stakeholders' practices and guide policy options. This research investigated how stakeholders conceptualise climate change in terms of its seriousness and related uncertainty, and a resilience approach as a possible policy option to confront this uncertainty. An application of the conceptual framework provided by Handmer and Dovers' typology of emergencies is novel to the climate change field. Results show that there is a tendency to frame climate change as complex (with uncertainty representing part of that complexity) and to confront this complexity with less complex policies and solutions. No pattern of a conceptual link between uncertainty and resilience was observed. The results presented in this study offer empirical evidence to inform theory and provide helpful insights to inform policy design and practice.